2022
DOI: 10.5852/cr-palevol2022v21a3
|View full text |Cite
|
Sign up to set email alerts
|

The Mesolithic of Atlantic Coastal Spain – a comparison with the Middle Ebro Basin

Abstract: This paper compares current evidence for Mesolithic adaptations along the north Spanish coast from Galicia in the west to the Basque Country in the east. Significant questions and issues pertinent to Mesolithic research are reviewed, followed by a brief discussion of advances in method and theory over the past 25 years. Cantabria, País Vasco, and Galicia are compared with each other and en bloc with evidence from the middle Ebro over the 12-6 ka BP interval considered to bracket the transition between foraging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Finally, different regional studies used time series analyses of summed probability distributions of calibrated radiocarbon dates (SPD) to discuss the impact of the 8.2k cal a BP climatic event on Iberian Mesolithic populations (Bernabeu et al, 2014 andMontes et al, 2016;Fyfe et al, 2019;Alday et al, 2018;Fernández-López de Pablo et al, 2019;McLaughlin et al, 2021;Clark and Barton 2022). These studies reported very different results: from studies identifying positive trends in demographic growth such in the Iberian Atlantic areas of Central Portugal (McLaughlin et al, 2021) and Asturias-Cantabria (Clark and Barton 2022), to others that do not identify a clear impact as in the Mediterranean area (Fyfe 2019) and the Ebro valley (Clark and Barton 2022;Alday et al, 2018), or those that, at subregional level, have identified both positive and negative trends (Fernández-López de Pablo et al, 2019;Bernabeu et al, 2016;Montes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, different regional studies used time series analyses of summed probability distributions of calibrated radiocarbon dates (SPD) to discuss the impact of the 8.2k cal a BP climatic event on Iberian Mesolithic populations (Bernabeu et al, 2014 andMontes et al, 2016;Fyfe et al, 2019;Alday et al, 2018;Fernández-López de Pablo et al, 2019;McLaughlin et al, 2021;Clark and Barton 2022). These studies reported very different results: from studies identifying positive trends in demographic growth such in the Iberian Atlantic areas of Central Portugal (McLaughlin et al, 2021) and Asturias-Cantabria (Clark and Barton 2022), to others that do not identify a clear impact as in the Mediterranean area (Fyfe 2019) and the Ebro valley (Clark and Barton 2022;Alday et al, 2018), or those that, at subregional level, have identified both positive and negative trends (Fernández-López de Pablo et al, 2019;Bernabeu et al, 2016;Montes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%